Implementation of Peer-Teaching Learning Methods to Improve the Students’ Learning Outcomes on Features of Modern/Contemporary Art - Arif Yulianto (International Journal of Multi Discipline Science, 2019)
This study aims to improve the students’ learning outcomes on features of modern/contemporary art after being implemented peer-teaching learning methods. This study is a classroom action research that consisted of two cycles. Each cycle consisting of planning, implementation, observation, and reflection. This study was conducted on students of class XII IPS1 the second semester of the academic year 2018/2019 in SMA Negeri 1 Wirosari, Wirosari District, Grobogan. Variables of this study was consisted of: (1) the control variable is students of class XII IPS1 with total of 37 people that consisted of 12 boys and 25 girls; (2) the independent variable in the form of cooperative learning model of peer-teaching learning methods; and (3) the dependent variable is students’ learning outcomes. The data collection technique in this study was done by using the test in the form of a written assessment test questions do with the end of each learning cycle and non-test technique by using the observations, interviews, and documentation. The results showed that the average value of students’ learning outcomes has increased, this is evidenced from the increase of students’ learning outcomes of Pre-Cycle with the average of 68.16 increased in Cycle I after being implemented peer-teaching methods becomes to 76.61, and eventually could be increased again in Cycle II into 89.28.